Foreign aid and economic growth in South Africa - Feudjou, Alain (Research of GSB, 2018)
Foreign aid inflows have grown significantly in the post-war period. Many studies have tried to assess the effectiveness of aid. The role of foreign aid in promoting economic growth has been the subject of much debate among development specialists, researchers, aid donors as well as recipients in general and South Africa in particular. In spite of this, there are only few empirical studies that investigate the relationship between foreign aid and economic growth in South Africa. This study assesses whether there is any existent relationship between foreign aid and economic growth in South Africa using descriptive statistics for data that spans from 1994 to 2010. The result supports the view that there is strong, positive and significant relationship between foreign aid and economic growth in South Africa. This implies that foreign aid contributes to economic growth in South Africa.